The Molecular Basis of the Anti-Inflammatory Property of Astragaloside IV for the Treatment of Diabetes and Its Complications - Li L; Zhang Y; Luo Y; Meng X; Pan G; Zhang H; Li Y; Zhang B (Dove Medical Press, 2023)
Lin Li,1- 3,* Yuwei Zhang,1,3,* Yudan Luo,1 Xianghui Meng,1 Guixiang Pan,4 Han Zhang,1- 3 Yuhong Li,1- 3 Boli Zhang1,3 1Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People's Republic of China; 2Ministry of Education Key Laboratory of Pharmacology of Traditional Chinese Medical Formulae, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People's Republic of China; 3State Key Laboratory of Component-Based Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People's Republic of China; 4Second Affiliated Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, 300250, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuhong Li; Boli Zhang, Tianjin University of Traditional Chinese Medicine, 10 Poyang Lake Road, Jing Hai District, Tianjin, 301617, People's Republic of China, Email yhltcm@126.com; zhangbolipr@163.comAbstract: Astragali Radix is a significant traditional Chinese medication, and has a long history of clinical application in the treatment of diabetes mellitus (DM) and its complications. AS-IV is an active saponin isolated from it. Modern pharmacological study shows that AS-IV has anti-inflammatory, anti-oxidant and immunomodulatory activities. The popular inflammatory etiology of diabetes suggests that DM is a natural immune and low-grade inflammatory disease. Pharmacological intervention of the inflammatory response may provide promising and alternative approaches for the prevention and treatment of DM and its complications. Therefore, this article focuses on the potential of AS-IV in the treatment of DM from the perspective of an anti-inflammatory molecular basis. AS-IV plays a role by regulating a variety of anti-inflammatory pathways in multiple organs, tissues and target cells throughout the body. The blockade of the NF-κB inflammatory signaling pathway may be the central link of AS-IV's anti-inflammatory effect, resulting in a reduction in the tissue structure and function damage stimulated by inflammatory factors. In addition, AS-IV can delay the onset of DM and its complications by inhibiting inflammation-related oxidative stress, fibrosis and apoptosis signals. In conclusion, AS-IV has therapeutic prospects from the perspective of reducing the inflammation of DM and its complications. An in-depth study on the anti-inflammatory mechanism of AS-IV is of great significance for the effective use of Chinese herbal medicine and the promotion of its status and influence on the world.Keywords: astragaloside IV, anti-inflammatory property, molecular basis, diabetes, complications